Determining the factors influencing tourist souvenir expenditure: The case of Turkey - Kızılcık, Onur; Birdir, Kemal (Turyzm/Tourism, 2023)
In this study, information will be explored that will contribute to increasing tourism income in destinations with low tourist expenditure per person. For this purpose, the souvenir expenditure of tourists in Turkey is examined. Souvenir stores in Sultanahmet and the Grand Bazaar in Istanbul were investigated using a qualitative case study research design. Semi-structured interviews were conducted with 11 souvenir sellers and 778 online comments of tourists shopping in souvenir stores were analyzed by netnography. As a result of the research, it has been determined that the efforts made to transform products based on the natural, historical and cultural richness of Turkey into brands, and thus increase local product diversity, play a critical role in increasing souvenir expenditure. On the other hand, the importance of the selection of high spending tourists as the target market and increasing the employment of qualified workers in the tourism sector has emerged.